Ensiled Wet Storage Accelerates Pretreatment for Bioconversion of Corn Stover - Essien, Dzidzor; Richard, Tom L. (Frontiers in Bioengineering and Biotechnology, 2018)
Organic acids produced during ensiled wet storage are beneficial during the storage process, both for biomass preservation and to aid in mild in-situ pretreatment. However, there is concern these acids could later have negative impacts on downstream processes, especially microbial fermentation. Organic acids can inhibit microbial metabolism or growth, which in turn could affect biofuel productivity or yield. This study investigated the interaction of organic acids produced during ensiled storage with subsequent pretreatment of the resulting corn stover silage, as well as the potential for interference with downstream ethanol fermentation. Interaction with pretreatment was observed by measuring xylan and glucan removal and the formation of inhibitors. The results indicated that organic acids generally do not impede downstream processes and in fact can be beneficial. The levels of organic acids produced during 220 days of storage jar tests at 23oC or 37oC, and their transformation during pretreatment, remained below inhibitory levels. Concentrations of individual acids did not exceed 6 g per liter of the pretreated volume, and less than 5% on a dry matter basis. Whereas unensiled corn stover required 15 minutes of 190oC pretreatment to optimize sugar release, ensiled corn stover could be treated equally effectively at a lower pretreatment duration of 10 minutes. Furthermore, the different organic acid profiles that accumulate at various storage moisture levels (35 ̶ 65%) do not differ significantly in their impact on downstream ethanol fermentation. These results indicate biorefineries using ensiled corn stover feedstock at 35% ̶ 65% moisture levels can expect as good or better biofuel yields as with unensiled stover, while reducing pretreatment costs.